Rhizophora apiculata Bark Ethanolic Extracts Prevent Kidney Damage Caused by Cigarette Smoke in Male Rats - Syazili Mustofa; Sarasmita Nirmala Dewi (Fakultas Kedokteran Universitas Sriwijaya, 2023)
Rhizophora apiculata mangrove bark contains high levels of antioxidants, including triterpenoids, steroids, saponins, and tannins. The high antioxidant content can prevent oxidative stress, one of which is caused by free radicals from cigarette smoke. This research aimed to determine the potential of Rhizophora apiculata mangrove bark to protect against damage to the kidney organs of male white rats (Rattus novergicus) of the Sprague-Dawley strain exposed to cigarette smoke. This study used 25 mice divided into 5 groups for 30 days, namely group K(-), which was not given exposure to cigarette smoke and mangrove bark extract; group K(+), which was only given exposure to cigarette smoke; group P1, which was given the extract mangrove bark with a dose of 26.27 mg/kg BW and given exposure to cigarette smoke 24 cigarettes per day, group P2 which was given mangrove bark extract with a dose of 56.55 mg/kg BW and given exposure to cigarette smoke 24 cigarettes per day, and group P3 which was given mangrove oil bark extract at a dose of 113.1 mg/kg BW and given exposure to cigarette smoke 24 cigarettes per day. On day 31, the rats were euthanized, and their kidneys were prepared for histology. Kidney histology was observed, and kidney damage was assessed from the histology of glomerular and renal tubular damage. The kidney damage score is 0 if there was no damage, 1 if inflammatory cell infiltration was found, 2 if Bowman space edema or swelling of tubular epithelial cells was found, 3 if necrosis was found. Then, take the average of each renal tubular and glomerular damage score and add them together for a total damage score, namely 0-6. The median kidney damage score in the K (-) group was 0.4, the K (+) group was 3.6, the P1 group was 2.4, the P2 group was 2.4, and the P3 group was 2.2. The results of the Kruskal-Wallis test obtained a p-value of 0.001, meaning there were significant differences in at least the two treatment groups. This research showed that administering Rhizophora apiculata mangrove bark extract could prevent histological damage to the kidneys of male white rats of the Sprague-Dawley strain caused by cigarette smoke.